Serum homocysteine is a valuable marker for predicting aggravation of infection in intestinal obstruction patients. Issue 1 (January 2023) - Zhu, Youlong; Liu, Ruming; Geng, Xuan; Zhang, Wentao; Li, Bingqiang; Ma, Cheng; Song, Tao; Xia, Hong; Quan, Bin
The aim of this study was to investigate the expression of serum homocysteine (HCY), procalcitonin (PCT), and C-reactive protein (CRP) in abdominal infectious disease and analyze their relationship with the degree of abdominal infection. We conducted a retrospective study involving 157 patients with abdominal infections at Xuzhou Central Hospital between January 2016 and October 2019. The patients were composed of intestinal obstruction (73 cases), appendicitis (45 cases), perforation of the digestive tract (25 cases), and cholecystitis (14 cases). The HCY, PCT, and CRP levels of patients with abdominal infections were detected using enzyme-linked immunosorbent assay (ELISA), and correlation analysis between the HCY, PCT, and CRP levels and abdominal infection was performed using Pearson's correlation analysis. Compared with before treatment, the HCY, PCT, and CRP levels in the four groups decreased significantly after treatment. The levels in the patients in the intestinal obstruction group decreased more markedly than in those in the other groups. There were positive correlations among the HCY level, PCT, and CRP before treatment only in patients with intestinal obstruction ( P  < 0.001). The difference was statistically significant in the HCY level between the non-operation and the operation groups in patients with intestinal obstruction ( P  < 0.001). Serum HCY may be a valuable marker for predicting aggravation of infection in patients with intestinal obstruction.